Deep-water scleractinian corals (Cnidaria: Anthozoa) from 2010-2011 INDEMARES expeditions to the Galicia Bank (Spain, northeast Atlantic) - Altuna, Alvaro (Zootaxa, 2017)
During surveys in the Galicia Bank (northeastern Atlantic) in the years 2010–2011 (INDEMARES project), 25 species of scleractinian corals corals were collected in a depth interval of 744–1764 m. Most interesting species are described and depicted. Additionally, species list and remarks are given for the 23 species dredged in the bank during the 1987 SEAMOUNT 1 expedition at 675–1125 m depth.From a literature review and new records from Galicia Bank given herein, 31 species of scleractinian corals are known from this seamount in a depth interval of 614–1764 m depth. Six are colonial and 25 solitary, with 17 occurring on hard bottoms and 14 on soft bottoms. Desmophyllum dianthus, Lophelia pertusa and Madrepora oculata are the most widely distributed species in both number of stations and depth range of specimens collected alive. Some species were recorded outside their previously known bathymetric ranges in the northeastern Atlantic. Javania pseudoalabastra is first documented for the Iberian Peninsula and Spanish faunas. Thrypticotrochus sp. is first collected from the Atlantic Ocean.